La devaluación del dólar vista desde la perspectiva histórica del Acuerdo del Plaza: una reflexión (2011)
This article seeks to convey the author's experience regarding the measures that Japanese companies took to combat the profound effects that the appreciation of the yen against the U.S. dollar had on their competitiveness and strategies put in place to try to recover their share in world markets and seek new sources of productivity and competitiveness in the second half of the 1980s and the 1990s, after signing the famous Plaza Accord. It also seeks to contrast, at different times, which has significance for the economies of Colombia and Japan the revaluation of their currencies, the peso and the yen, in the international environment.